Aid and the environment: The case of Kenya - Wilfred Nyangena (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
We investigate allocations of foreign aid by donors to the environment sector in Kenya covering the period 2001-12. Our data are largely obtained from official government and global aid databases complemented with donor interviews. We find that donor funding remained significant with emphasis on economic sectors such as agriculture, industry infrastructure and public debt. Allocations to environment have not been priority for donors in spite of several policy statements. Further, aid flows remained unpredictable, with huge disbursements occurring as emergency funds during disasters.
Keywords: F35; F64; O55; 330; foreign aid; environment; Kenya